Pengaruh Penggunaan Power Point Berbasis Animasi terhadap Hasil Belajar Siswa pada Materi Dimensi Tiga - Salmun K. Nasib; Abas Kaluku; Abdul Wahab Abdullah (Department of Mathematics, Universitas Negeri Gorontalo, 2020)
This article discusses the use of PowerPoint animation in learning with the aim of knowing the differences in learning outcomes of students whose learning uses power points and without using power points in three-dimensional topics. The method used is an experimental design with a True Experimental Design, namely Posttest-Only Design. The sampling technique used cluster random sampling. Student learning outcomes data were obtained through the learning outcome test instrument in the form of essays. Data analysis using descriptive analysis techniques and inferential data analysis. Hypothesis testing using a parametric analysis t-test. The results of the analysis show that the average learning outcomes of students who are taught using power points are higher than those of students taught conventionally. One of the factors that support the improvement of student learning outcomes is a learning approach to geometric shapes that involves interesting visualization. Interesting visualization makes students not just imagine something abstract but can directly observe the object being studied.